Current strategies in diagnostics and therapeutics against novel coronavirus disease (COVID-19) - ALOTAIBI FAISAL (Acta Pharmaceutica)
The epidemic of COVID-19 spread quickly through China and engulfed all of the countries across the globe. Several advances have been made in understanding the novel coronavirus’s pathophysiology and in the development of newer diagnostics with pinpoint accuracy. Several newer therapeutic methods have either been accepted or are awaiting acceptance. In many countries, vaccination programs have been rolled out. Despite all these efforts, coronavirus still exists, though with lesser propensity. Multiple new forms of the novel coronavirus unexpectedly appeared in various areas of the world, undermining previously existing diagnosis and care protocols. This article highlights our understanding of the novel coronavirus’s symptoms in brief, pathogenesis, diagnostics, and therapeutic strategies to contain COVID-19. The clinical findings, including serological, radiological, and other advanced diagnostic strategies, contributed much to control the disease. To date, supportive interventions have been used in tandem with potent antiviral therapies such as remdesivir, lopinavir/ritonavir, or corticosteroids with a level of trust in the care of COVID-19 patients. However, in several areas of the world, vaccination initiatives took place; the vaccines’ safety and efficacy to control the outbreak is yet to be identified. This review concludes that improvement in therapies and diagnostics for COVID-19 must continually be explored as new variants constantly emerge.